Test Case Automation Using Natural Language Processing - Mahajann, Saurabh; Mulchandani, Mona; Ajani, Samir (International Journal of Computer Sciences and Engineering, 2025)
Software testing is an integral part of the software development life cycle. In order to achieve the testing on individual module or complete integration testing of the system a quality analyst makes test cases for it, covering the different scenarios against which validity of the working of the system is checked. A test case is nothing but a set of conditions and data with it under with it a quality analyst will test a system and check if working according to specification or not. More focus is made on automating the testing of the software, resulting in the creation of the several automation testing framework such as Selenium, Apache Jmeter etc. Similarly attention on creating the test cases is also made. As user stories are written in the natural language, natural language processing can be a way of extracting information from it. Conformiq provides the same functionality. In agile development methodology such as extreme programming such automation is really advantageous which provided quite flexibility and adaptive to change provided.